Analisis Efektifitas Strategi Investasi Strategi Investasi DFogs of the Dow pada Saham LQ45 - , Anindya Himmah Ramdyanti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The popular investment strategy âdogs of the dow â has been introduced by O'Higgins in 1991 and applied to the 30 stocks in the Dow Jones Industrial Average (DJIA). The strategy is done by forming a portfolio that has the highest dividend yield, and shown to have a higher average annual return than the return of the DJIA during the period 1973-1998. A similar study has been done in the capital markets of India and China. Accordingly, this study intends to evaluate the implementation of dogs of the dow strategy in Indonesia capital market. The author applies the strategy of dogs of the dow on LQ45 stocks by forming a portfolio with the highest dividend yield. The portfolio is well maintained and evaluated in every year, every second year, and the fifth, and every five years at a time. Risk and return of a portfolio is compared with the risk and return of the LQ45 index and the stock index, and evaluated by the method of Sharpe, Treynor, and Jensen. During the period 2007-2011, the dogs of the dow portfolio has an average return that can beat the market. Although most have a greater degree of risk than the market, but by using the Sharpe index, Treynor, and Jensen obtained results where the portfolio has performed better than the market.